2023
DOI: 10.3390/foods12112182
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Composition and Consumer Acceptability of Amaranthus Leaf Powder Supplemented Ujeqe for Improved Nutrition Security

Abstract: Malnutrition, especially micronutrient deficiency, is a widespread health challenge that predominantly affects young children, young ladies who are within the productive age, refugees, and older adults who reside in rural communities and informal settlements in underdeveloped and developing countries. Malnutrition is caused by consuming either too little or too much of one or more food nutrients. Additionally, monotonous dietary lifestyle, especially the over-reliance on staple foods, is identified among the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
(92 reference statements)
0
3
0
Order By: Relevance
“…It is interesting to note that bakery products are one of the most consumed food groups worldwide, with refined wheat flour being the main ingredient. However, refined flour has a high glycemic index and despite its excellent technological characteristics for bakery products, its use as an ingredient imposes restrictions on individuals suffering from pathologies associated with its intake [79,80]. This makes the inclusion of fruit co-product flours in bakery products, such as breads, cakes, and cookies, an interesting alternative for improving the nutritional and functional profile of these products [71,81].…”
Section: Study Results Referencesmentioning
confidence: 99%
“…It is interesting to note that bakery products are one of the most consumed food groups worldwide, with refined wheat flour being the main ingredient. However, refined flour has a high glycemic index and despite its excellent technological characteristics for bakery products, its use as an ingredient imposes restrictions on individuals suffering from pathologies associated with its intake [79,80]. This makes the inclusion of fruit co-product flours in bakery products, such as breads, cakes, and cookies, an interesting alternative for improving the nutritional and functional profile of these products [71,81].…”
Section: Study Results Referencesmentioning
confidence: 99%
“…To gain insights into consumer preferences and acceptability criteria, consumer-oriented testing methods and untrained sensory panels have proven to be a valuable approach [41,42]. In order to assess the consumer acceptance and preference information for the formulations treated with chia protein hydrolysates in a wheat bread, the B10 formulation, which had highest amount of hydrolysate per gram of flour, was selected for a further preliminary sensory analysis [43].…”
Section: Sensory Test: Consumer Acceptability Of Selected Bread Forti...mentioning
confidence: 99%
“…Bone characteristics and fracture strength were improved in tortilla-fed groups, and the study suggested that OH could be a sustainable method for tortilla production while maintaining a nutritional value comparable to that of traditional methods. Olusanya et al [16] discussed the potential of enriching staple foods such as Ujeqe with Amaranthus leaf powder (ALP) to enhance the mineral content to mitigate a malnutrition situation. The study found that ALP supplementation increased protein, ash, and certain mineral content, but higher ALP concentrations led to a lower consumer acceptability of Ujeqe.…”
mentioning
confidence: 99%